Higher Education, Social Mobility and Social Class: Importance of Habitus and Capitals when Analysing Student Choice and Transitions - Schofield, Lindsay Michelle; Takriti, Rachel; Atkinson, Susan (International Journal of Educational and Life Transitions, 2023)
Extensive literature spanning decades articulates the complexities for young people from ‘lower socioeconomic communities’ in the decision-making process surrounding education – possibly highlighting how Widening Participation (WP) policy and practice, is not necessarily reducing socioeconomic inequalities, and contributing to social mobility. Arguing for the crucial role of cultural, social, and economic capital to be considered in educational policy-making, this article examines the educational and transitional experiences of students from lower socioeconomic communities within the United Kingdom (UK), moving to Higher Education (HE). Bourdieu’s conceptual toolkit (habitus, agency, and capitals) is operationalised in reference to the data, to unravel the fraught relationship of habitus and choice or more specifically ‘free choice’. Through the use of focus groups, the research suggests that despite governmental optimism and policy the presence of anxiety and fear in young people from lower socioeconomic communities, in applying to HE, is multifaceted. This article highlights that despite students demonstrating a determination and aspiration in the transition from Further Education (FE) to HE, the idea of ‘choice’ remains widely problematic for the under-represented. The article urges educators and policy-makers to rethink the complexities of choice concerning student transitions when opportunities in terms of life trajectories remain governed by social class boundaries.
Keywords: Lower Socioeconomic; Bourdieu; Choice; Transition; Mobility; Capital